PREVELENACE OF LOW BACK PAIN AMONG NURSES WORKING IN ELMAK NIMER UNIVERSITY HOSPITAL – SHENDI - SUDAN 2015 - Al-samawi, MuaadhAbdulghaniGhaithan; Abdallah Awad, Higazi Mohammed Ahmed (International Journal of Research -GRANTHAALAYAH, 2015)
Globally, Low Back Pain (LBP) comprises a significant occupational hazard in nursing profession. Objectives: To estimate the incidence, to identify risk factors, and impact of illness of LBP among nurses in AL-MakNimer university Hospital at Shendi city. A cross-sectional study was applied including nurses in AL-MakNimer university Hospital at Shendi city, republic of Sudan throughout the period May -June, 2015. Sample was chosen by using total coverage sample. A predesigned questionnaire was used for data collection. The questionnaire included demographic data, work-related factors as well as effect and management of LBP data obtained were analyzed using manually and by used SPSS soft program. Results: The results revealed that the overall incidence of low back pain among nurses was (n=70, 87.5%) Female participants complaining of LBP were significantly more than male participants (85%) of the total female reported LBP. There were significantly relate between age and working hours (.015) it can be seen that about (40%) of the participants experienced LBP at least once a week or more frequently. 52.9% subjects rated their pain as moderate pain. 35.7% nurses’ concept regarding factors contributing to their LBP were lifting as well as 28.6% working load,(52.9%) sleep disturbance, (64.3%) restrict activities were nurse comment regarding LBP effect. LBP is a common health problem among working nurse, lifting, work load, were the most perceived work-related risk factors for LBP, restrict activities, taking many days off, might be the most predisposed effect related to LBP. Recommendation: These findings suggest that hospitals should focus and attempt to improve the ergonomics of nursing activities. In addition, effective methods of implementing changes in work systems are needed.